2019
DOI: 10.1016/j.celrep.2019.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Hair Growth by Small Molecules that Activate Autophagy

Abstract: Highlights d mTOR and AMPK modulation by rapamycin, metformin, and a-KG induces anagen hair growth d Autophagy induction is necessary and sufficient for anagen entry and hair growth d Autophagy is increased during anagen phase of the natural hair follicle cycle d Aged mice fed the autophagy-inducing metabolite a-KB are protected from hair loss

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 63 publications
0
101
1
Order By: Relevance
“…Recently, small molecule activators of autophagy, such as alpha-ketoglutarate and alpha-ketobutyrate, were reported to induce a switch from telogen (the quiescent phase of the hair cycle) to anagen (the phase of active hair growth) in mice (Chai et al, 2019). Similarly, rapamycin and metformin stimulated growth of hair and their effects could be blocked by autophinib, an inhibitor of autophagosome formation (Chai et al, 2019). Studies in mouse models of alopecia and in humans are needed to determine whether the pharmacological activation of autophagy is able to counteract hair loss.…”
Section: Autophagy In Epithelial Cells Of the Skinmentioning
confidence: 99%
“…Recently, small molecule activators of autophagy, such as alpha-ketoglutarate and alpha-ketobutyrate, were reported to induce a switch from telogen (the quiescent phase of the hair cycle) to anagen (the phase of active hair growth) in mice (Chai et al, 2019). Similarly, rapamycin and metformin stimulated growth of hair and their effects could be blocked by autophinib, an inhibitor of autophagosome formation (Chai et al, 2019). Studies in mouse models of alopecia and in humans are needed to determine whether the pharmacological activation of autophagy is able to counteract hair loss.…”
Section: Autophagy In Epithelial Cells Of the Skinmentioning
confidence: 99%
“…To assess whether Sirt7 regulates adult hair growth, we shaved the hair coat of female Sirt7 +/+ and Sirt7 À/À mice on postnatal day (P) 60, when the HFs of both genotypes were in the second telogen phase ( Fig 1A). We evaluated hair coat recovery based on skin pigmentation and hair shaft growth as described Chai et al, 2019). By P120, Sirt7 +/+ mice recovered an almost full hair coat, while the Sirt7 À/À mice showed only~25% recovery (Fig 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Hair cycle analyses were based on skin pigmentation, as previously described . In brief, shaved hair coat recovery values from 0 to 100% were calculated based on skin pigmentation levels and hair shaft density (Chai et al, 2019). For example, 0% indicated no hair growth (and no pigmentation); 50% indicated fulllength hair growth on 50% of the dorsal skin area or pigmentation on 100% of the dorsal skin area without hair shafts; 70% indicated full-length hair growth on 70% of the dorsal skin or pigmentation on 100% of dorsal skin with 30-40% hair shafts; 100% indicated full-length hair growth on 100% of the dorsal skin.…”
Section: Hair Cycle Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A second, more recent article, provides additional support to the importance of autophagy. [ 73 ] This time utilizing a murine model (C57BL/6J mouse), the authors demonstrate that autophagy increases during anagen phase of the normal hair cycle, is reduced during catagen and remains low during telogen. Furthermore, using several compounds that induce autophagy, including the metabolite α‐ketoglutarate and the mTOR inhibitor rapamycin, it was demonstrated that treatment of HFs in telogen phase resulted in accelerated HF regeneration.…”
Section: Autophagy As An Element Of Hair Growth Controlmentioning
confidence: 99%